Enhancing Resilience in Autistic Adults Using Community-based Participatory Research: A Novel HRD Intervention in Employment Service Provision. Issue 4 (November 2020) - Farkas, Tibor N.; Mendy, John; Kargas, Niko
The Problem: Although previous research suggests current human resource management (HRM) policies and procedures do not fully accommodate the diverse strengths and needs of jobseekers and employees on the autism spectrum, the human resource development (HRD) community, including its scholars, researchers and practitioners will benefit from learning more about autism and how people with the condition can develop resilience capacity at work. The Solutions: Utilizing a community-based participatory research approach (CBPR), we recommend an Autism Work Peer Support Group (AWPSG) program as a new framework that can help the HRD community as well as HRM work coaches and disability employment advisors to foster environments, where people's social adaptation is key for their resilience capacity development. The Stakeholders: The current research provides a framework on how a CBPR approach could be utilized to operationalize the design and evaluation of an employment intervention (i.e., AWPSG) that could involve autistic jobseekers in the process of resilience building. Furthermore, our findings indicate that fostering the emergence of a subjectively meaningful employment-focused peer support group program could help enlighten the HRD community about the challenges faced by this particular group and thereby offer effective autism-HRD advice and support to autistic jobseekers, employees and employers, management, work-coaches and disability employment advisors.